Arthroscopical Reinforcement of an Isolated Insufficiency of the Radioscaphocapitate Ligament to Treat Dynamic Radioscaphoid Instability: A Case Report - Goorens, Chul Ki; Debaenst, Niels; Van Royen, Kjell (Journal of Hand and Microsurgery, 2023)
The radioscaphocapitate ligament is part of the stabilizatory complex of the scaphoid. Isolated injury resulting in persistent radioscaphoid instability is rarely reported. The authors propose a technique for arthroscopic reinforcement. Magnetic resonance, dynamic fluoroscopy, and wrist arthroscopy will confirm the elongation of radioscaphocapitate ligament. Under arthroscopic control, an anchor can be drilled into the radial aspect of the scaphoid to tension the ligament toward the anchor. An arthroscopic reinforcement of the radioscaphocapitate ligament may resolve a persistent radioscaphoid instability due to elongation.
Keywords: wrist arthroscopy; radioscaphocapitate ligament; extrinsic ligaments; reinforcement; instability